Adenocarcinoma of the ampulla of Vater. A 28-year experience. - Talamini, M A (1997)
OBJECTIVE: The aim of this study were to review the experience with adenocarcinoma of the ampulla of Vater at The Johns Hopkins Hospital and to determine what factors influenced the long-term outcome in these patients. SUMMARY BACKGROUND DATA: Adenocarcinoma of the ampulla of Vater is the second most common periampullary malignancy. However, most series have relatively small numbers. As a result, analysis of factors influencing outcome has been limited. METHODS: From 1969 to 1996, 120 patients with adenocarcinoma of the ampulla of Vater were managed at The Johns Hopkins Hospital. Clinical, operative, and pathologic factors were correlated with morbidity and long-term survival. Factors influencing outcome were evaluated by univariate and multivariate analyses. RESULTS: Resection was performed in 106 patients (88%), and 105 of these patients (99%) underwent either pancreatoduodenal resection (n = 103) or total pancreatectomy (n = 2). Resection rate increased from 62% in the 1970s to 82% in the 1980s to 96% in the 1990s (p < 0.05). Overall mortality after resection was 3.8% with no mortality in the 45 consecutive patients resected in the past 5 years. Morbidity also decreased significantly (p < 0.05) from 70% before to 38% after December 1992. Five-year survival for resected patient was 38%. Factors favorably influencing long-term outcome were resection (p < 0.001), no perioperative blood transfusions (p < 0.05), negative lymph node status (p = 0.05), and moderate or well-differentiated tumors (p < 0.05). In a multivariate analysis, the best predictor of prolonged survival was absence of intraoperative transfusion (p = 0.06, relative risk = 1.90, 95% confidence limits = 0.95-3.78). CONCLUSIONS: Compared to carcinoma of the pancreas, carcinoma of the ampulla of Vater has a higher resectability rate and a better prognosis. Early diagnosis is important because lymph node status influences survival. Careful operative dissection and avoidance of transfusions also improves long-term survival.